Expression of genes involved in the anthocyanin biosynthesis pathway in white and red fruits of Fragaria pentaphylla and genetic variation in the dihydroflavonol-4-reductase gene. (June 2017) - Duan, Wenkai; Sun, Peilong; Li, Junmin
Abstract: Structural and regulatory genes control fruit colors in plants. Real-time quantitative PCR results showed significantly higher expression levels of structural genes ( FpCHS, FpDFR, FpANS, and FpUFGT ) as well as of the regulatory gene MYB10 in red fruits of Fragaria pentaphylla compared to white fruits. These genes were strongly associated with anthocyanin accumulation within fruits. The full-length sequence of the FpDFR gene in red fruits of F. pentaphylla had a length of 2080 bp, was separated by five introns, and shared 95% homology with the F. vesca DFR sequence. Twenty-seven SNPs were detected in the FpDFR gDNA sequences between red and white fruits. Among these, transition substitutions were more frequent than transversions (66.7% vs. 33.3%), and a larger number of nucleotide variants existed in introns compared to exons (70.4% vs. 29.6%). A Chi-square test showed only three SNPs significantly associated with fruit color. Combined with structural analyses of the Fp DFR protein and an expression analysis of the anthocyanin pathway genes, these results indicate that trans -regulation might contribute to color control in F. pentaphylla . Graphical abstract: Highlights: First demonstration of associations between gene expression and fruit color in Fragaria pentaphylla . cDNA and gDNA of FpDFR gene of Fragaria penthaphylla were isolated, sequenced and analyzed. Twenty-seven SNPs were detected in the FpDFR gDNA sequences between red and white fruits of Fragaria pentaphylla. Three SNPs significantly associated with fruit color.